International labor standards concerning collective bargaining in public services - Canessa Montejo, Miguel Francisco (2019)
International Labor Standards recognize the right to collective bargaining of public servants and officials, allowing for the exclusion of high-level employees (with policy-making power, managerial positions or positions based on trust) and members of the armed forces and police. The negotiation topics cover the conditions of work and employment, which includes salary negotiation. The principle of budget balance is a valid limit to collective bargaining.